2019
DOI: 10.2478/arsm-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Dysfunction Prevalence in Parkinson Disease Patients

Abstract: The goal of this study was to estimate the prevalence of patient-reported genitourinary dysfunction symptoms in Parkinson’s disease patients from the Southeastern Romania. The study was performed on 86 patients with idiopathic Parkinson’s disease from 5 Outpatients Clinics of Constanta, 56% males, mean age 70.6 years, mean disease duration 6.33 years. The patients have been assessed for the presence of genitourinary symptoms using the Scale for Outcomes in Parkinson’s Disease for Autonomic Symptoms (SCOPA-AUT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One study revealed that the patients without residual urine were younger than patients with residual urine (67.5 vs. 70.1 years) (Zhang and Zhang, 2015 ). A higher weighted prevalence was calculated in older people than younger people (76 vs. 18%) (Campos-Sousa et al, 2003 ; Irene, 2019 ), suggesting PD patients with older age might be more likely to experience urinary retention. Overall, when distinguishing PD from MSA with urinary retention symptoms, we should be more cautious and consider relevant factors such as age, disease duration, and disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study revealed that the patients without residual urine were younger than patients with residual urine (67.5 vs. 70.1 years) (Zhang and Zhang, 2015 ). A higher weighted prevalence was calculated in older people than younger people (76 vs. 18%) (Campos-Sousa et al, 2003 ; Irene, 2019 ), suggesting PD patients with older age might be more likely to experience urinary retention. Overall, when distinguishing PD from MSA with urinary retention symptoms, we should be more cautious and consider relevant factors such as age, disease duration, and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…PD patients were generally considered less likely to develop those two symptoms, and the presence of unexplained voiding difficulties with elevated post-void residual (PVR) volume ≥ 100 ml or unexplained urinary urge incontinence was often considered to support the diagnosis of multiple system atrophy (MSA) (Yamamoto et al, 2016 ; Wenning et al, 2022 ). However, urinary incontinence and retention are not rare, even PVR volume ≥ 100 ml can also occur in PD (Irene, 2019 ; Tateno et al, 2021 ). For example, one study with large sample size found that the prevalence of urinary incontinence was 43% in PD (Wüllner et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation